Cultural care practices among mothers of nurslings with respiratory infection - Dayanne Rakelly de Oliveira; Gabriela Bezerra Dantas (Universidade de Fortaleza, 2012)
Objective: To understand the cultural practices of care among mothers of infants with respiratory infection in a pediatric outpatient clinic, from the recognition of the importance of the use of traditional medicine in Brazil. Methods: We applied a descriptive and exploratory study, qualitative, with twenty-eight mothers of infants with respiratory infection seen at a referral center in the city of Barbalha - CE, Brazil. Data were collected between the monthsof November and December of 2010 through semi-structured interview with a tape recorder. The speeches were analyzed by thematic-categorical analysis, which allowed the creation of four themes: cultural practices of care among mothers, sources of information on medicinal plants, modes of preparation of medicinal herbs and plants used by mothers. To ensure anonymity of participants, they received enumeration following the order of interviews. Results: The study showed that mothers make use of folk medicine, through the preparationof home remedies in order to treat and cure respiratory infections of their children; the leaking tea and herbal medicine are worth mentioning. Mothers place great confidence and give real meaning to the use of homemade preparations. It was observed that this knowledge comes from their mothers, grandparents, relatives and neighbors. Conclusion: Mothersattach great importance to popular practice, the traditional knowledge of relevant culturalvalue, as it is transmitted from generation to generation and has been rebuilt over time.